Outcomes of anterolateral thigh free flap thinning using liposuction following lower limb trauma - Askouni, E; Topping, A; Hettiaratchy, S; Nanchahal, J; Jain, A; Ball, S (2012)
Background: Whilst soft tissue closure is the priority to prevent infection in open fractures of the lower limb, some patients find that bulky flaps interfere with function and dislike the appearance. We report the outcomes of delayed free anterolateral thigh flap thinning with liposuction. Material and methods: 38 patients treated between 2006 and 2009 were offered flap contouring. 23 chose flap thinning and 15 did not. We measured outcomes using the SF-36v2 questionnaire and cosmetic outcome scores pre and postoperatively at a mean follow up of 12 weeks (range 10-16 weeks). Results: SF-36v2 physical health (PH) scores improved from a mean of 67 preoperatively to 80 postoperatively (p = 0.01) in the thinned group, while mental health (MH) scores remained unchanged (74-72). The mean SF-36v2 scores for the non-thinned group were 77 (PH) and 86 (MH). Following liposuction the median cosmetic outcome scores out of 5 improved from 1 (not at all satisfied) to 4 (very satisfied) postoperatively (p = 0.0005), which was also higher than the non-thinned group (3) [moderately satisfied], p = 0.004). There was no difference in sex, age, BMI and region on the leg of free flap reconstruction between the non-thinned and thinned groups. Conclusions: Delayed contouring of free ALT flaps used for lower limb reconstruction results in improvements in physical health measures and cosmetic outcomes. Patients not requesting thinning are generally satisfied with their reconstruction. © 2011 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.